Magnetic properties of Fe-Mo-5Ni-0.05C alloys with different contents of Mo - Abreu, Hamilton Ferreira Gomes de (1999)
Magnetic properties such as coercive force Hc, remanent induction Br, squareness Br/Bs and maximum energy product BHmax for alloys with Fe–5Ni–0.05C and 11, 15 and 19wt% of Mo were determined for samples cold rolled 60, 80%, 90 and 97% followed by magnetic aging at 610°C for 1h. The results show that the addition of carbon to alloys with 11 and 15wt% of Mo improves coercive force Hc and the amount of Mo has a significant role on remanent induction Br and squareness Br/Bs. After 97% of cold rolling and magnetic aging, an alloy with 11wt% of Mo reaches Hc=290Oe, Br=17 800G, Br/Bs=0.94 and BHmax=3.4MGOe. Values obtained for Hc, Br/Bs and BHmax are higher than those obtained by Jim et al. [J. Appl. Phys. 52 (3) (1981) 2503] in an alloy with 20% of Mo without carbon.